Efficacy of injection therapies in reducing hemiplegic shoulder pain: a systematic review and meta-analysis - Nie, Jing; Zhou, Hang; Du, Shenao; Zhang, Haowei; Liu, Yiying; Wei, Xiangyang; Ning, Wenhua; Wang, Haiming (Frontiers in Neurology, 2025)
ObjectiveThis systematic review of randomized controlled trials (RCTs) with meta-analysis aimed to investigate the efficacy of injection therapies in reducing hemiplegic shoulder pain (HSP) in stroke survivors.MethodsPubMed, Embase and the Cochrane databases were searched from inception to April 20, 2025 to identify RCTs of stroke survivors with HSP undergoing injection therapies to reduce pain intensity. The main outcome of the assessment was the degree of pain relief as measured by visual analogue scale (VAS). And the secondary outcome indicator is the range of motion (ROM) at the end of the follow-up period.ResultsA total of 408 results were identified by the search strategy, and 11 studies were included in the final analysis. We analyzed data for 353 stroke survivors with HSP, the results showed improvement of VAS within 4 weeks after injection was MD −1.03, 95% CI [−1.72, −0.33], p < 0.05, with large heterogeneity (I2 = 57%), and the improvement of VAS within 12 weeks after injection was MD −1.43 95% CI [−1.92, −0.94], p < 0.05, with no heterogeneity (I2 = 0%), significantly attenuated HSP. The improvement in shoulder external rotation ROM within 4 weeks after injection was MD 11.68, 95% CI [7.20, 16.15], p < 0.05, I2 = 0%, and the improvement within 12 weeks after injection was MD 10.00, 95% CI [5.78, 14.21], p < 0.05, I2 = 0%. The improvement in shoulder abduction ROM within 4 weeks after injection was MD 9.46, 95% CI [3.27, 15.64], p < 0.05, I2 = 0% while the improvement within 12 weeks after injection was MD 12.15, 95% CI [5.57, 18.73], p < 0.05, I2 = 7%.ConclusionThis systematic review and meta-analysis indicated that the addition of injection therapies to conventional rehabilitation is more effective than conventional rehabilitation alone in the complex treatment of patients with HSP in terms of both the short-term and long-term follow-up.Systematic review registrationThe protocol for this systematic review and meta-analysis was prospectively registered with PROSPERO (CRD420251040988).